Environmental performance of a geothermal power plant using a hydrothermal resource in the Southern German Molasse Basin. (April 2021) - Menberg, Kathrin; Heberle, Florian; Bott, Christoph; Brüggemann, Dieter; Bayer, Peter
Abstract: Every technology and anthropogenic activity affects the environment. This even applies to renewable, green energy forms, such as geothermal energy, which are often labelled as being climate neutral. Yet, a second glance reveals that this is not the case, as the construction, operation and decommissioning of geothermal power plants implies a consumption of materials and energy. Life Cycle Assessments (LCA) help to identify and quantify these impacts in order to ensure realistic comparability at different levels. Despite a growing number of surveys, however, either not all influencing parameters are explicitly considered, or the studies are only theoretical and based on generic data. Therefore, this study explores the binary plant of Kirchstockach located in Southern Germany in a comprehensive LCA. Corresponding scenarios identify leakages of used refrigerants and allocations of energy consumption during construction and operation as relevant impact factors. Results show that using refrigerants with low global warming potential ensures minimal effects even in case of larger losses. In addition, resource-saving drilling with electricity instead of diesel can effectively offset energy needs by later electricity production. In contrast, auxiliary energy usage from an electricity grid dominated by fossil sources has highly negative effects on the environmental performance. Graphical abstract: Image 1 Highlights: A comprehensive life-cycle assessment of a geothermal power plant is performed. Scenario analysis of refrigerant leakage and auxiliary energy supply schemes. Climate-friendly refrigerants offset negative effects in case of larger leakages. Accounting for self-supply of auxiliary energy needs is a crucial factor. Environmental impacts from hydrothermal plants are similar to enhanced systems.